Fruit shells of Camellia oleifera Abel as natural colourants for pigment printing of cotton fabric. Issue 1 (3rd January 2017) - Nakpathom, Monthon; Somboon, Buppha; Narumol, Nootsara; Mongkholrattanasit, Rattanaphol
Abstract : Purpose: The present study aims to focus on the feasibility of using an aqueous extract from the fruit shell of Camellia oleifera Abel as a source of natural colourant in printing-paste preparation for pigment printing of cotton fabric. The effects of pre- and post-mordanting with three common metallic mordants, that is AlK(SO4 )2, CuSO4 and FeSO4 on colour yield and colour fastness properties are also investigated. Design/methodology/approach: The printing paste was prepared by mixing the concentrated Camellia oleifera Abel fruit shell extract solution with commercially available synthetic thickener and binder. The fabric sample was printed with the prepared printing paste using a flat-screen printing technique. To determine the effects of pre- and post-mordanting, AlK(SO4 )2, CuSO4 and FeSO4 mordant aqueous solutions with various concentrations were applied using the pad-dry technique. Comparisons between printing with and without mordants were evaluated in terms of colour strength ( K/S values) and colour fastness to washing, light, crocking and perspiration. Findings: Without the mordants, the printed fabric had a yellowish brown shade with acceptable colour fastness properties, that is fair to good wash fastness, moderate light fastness, good to very good crocking fastness and fair to good perspiration fastness. The use of mordants, especially CuSO4 and FeSO4, not only enhanced colour strength but also imparted different colours to the fabric. Compared to the unmordanted fabrics, colour fastness properties were mostly comparable or improved in the mordanted fabrics depending on the type and concentration of mordants. Research limitations/implications: Although in the case of CuSO4 the light fastness was increased to a good to very good level, it is recommended that the final print be produced with a concentration of less than 0.125 gL −1 to yield the print with the residual amount of Cu metal under the limit, that is less than 50 ppm as regulated by the Oeko-Tex ® standard. Practical implications: The obtained prints from Camellia oleifera Abel fruit shell extract provided shades with satisfactory colour fastness to washing, light, crocking and perspiration. The extract from Camellia oleifera Abel fruit shell has the potential to be used as an alternative to synthetic dye in the textile industry. Originality/value: The use of Camellia oleifera Abel fruit shells, which are considered as abundant byproducts of tea seed oil production, as natural colouring agents for pigment printing of cotton fabric has been reported for the first time. It will minimise the environmental impact of this waste and create more valuable textile products.